Developing Creativity in Improving Education in Madrasas and Islamic Boarding Schools in Desah Bah Aren to Increase Competitiveness in the Modern Era - Sembiring, Ari Wibowo; Tanjung, Amaluddin; Yunita, Era; Sibarani, Lola Amalia; Rafsanjani, Akbar; Situmorang, Mela Safitri (Edumaspul: Jurnal Pendidikan, 2023)
This article examines efforts to develop creativity in the context of education in madrasas, Islamic boarding schools, in Baharen village with the main aim of increasing competitiveness in the modern era. This research explores educational strategies, methods and practices that can stimulate student creativity in traditional and rural Islamic educational environments. The research results show that the application of innovative approaches in the teaching and learning process, community involvement, and the use of technology contribute significantly to improving the quality of education and creativity of the younger generation. These findings provide important insights into how education can play an important role in preparing students to compete in the ever-changing modern era.